Induction of the Platelet Release Reaction by 1.3-Dimethyl-5-Aminoadamantane, a New Adamantane Derivative - Haacke, Uta; Wesemann, Wolfgang (Thrombosis and Haemostasis, 1977)
The amantadine derivative 1.3-dimethyl-5-aminoadamantane, D 145, induces in high concentrations of 2–10 mM the release reaction. Adenine nucleotides and 5-hydroxytryptamine (5-HT) are liberated to the same extent and in the same ratio as found after thrombin-induced release. The time course of release is very slow; maximal release is reached in 15–20 min. The process is temperature-dependent and dependent on energy derived from glycolysis and oxidative phosphorylation. Extracellular Ca++ does not promote the release process. D 145, in accordance with the mother-substance amantadine, inhibits 5-HT uptake non-competitively, KI = 0.15 mM. In concentrations of 0.1–1 mM D 145 triggers only the liberation of 5-HT, adenine nucleotides are not liberated. The ADP induced platelet aggregation is completely inhibited after preincubation with a 1 mM solution of D 145.